Primary Headache Associated with Sexual Activity in Adolescents: Illustrative Cases - Patel, Jinal; Rothner, David A. (Journal of Pediatric Neurology, 2021)
Primary headache associated with sexual activity (PHASA) is well described in adults, but reports in adolescents are lacking. PHASA is likely underreported in adolescents. A delay in or an absence of timely and adequate treatment has the potential to negatively impact normal adolescent psychosexual development. Physicians should consider this disorder in adolescents presenting with headaches, and understand the characteristics, diagnosis, and treatment. We reported two cases of PHASA in adolescents and review the epidemiology, presentation, and management.
Keywords: case report; sexual activity; adolescent health; headache